واقع استخدام ممارسات المحاسبة الإدارية دراسة مسحية في المنشآت الزراعية السورية العامة - زيود لطيف; العثمان محمد نادر; حاتم إياد مالك (Latakia University Journal - Economic and Legal Sciences Series, 2013)
هدفت الدراسة إلى اكتشاف مدى استخدام ممارسات المحاسبة الإدارية في المنشآت الزراعية السورية العامة وأهمية هذا الاستخدام، فضلاً عن معرفة أي من تلك الممارسات الأكثر شيوعاً وأهمية، وتحديد معوقات هذا الاستخدام إن وجدت. لذلك تم إجراء مسح ميداني باستخدام الاستبانة على منشآت القطاع الزراعي العامة في سورية, حيث تم توزيع /42/ استبانة على هذا المجتمع, تم استرجاع /26/ استبانة منها, وقد أظهرت نتائج تحليل البيانات أن هناك ضعفاً كبيراً ومستوى متدنياً في تطبيق ممارسات المحاسبة الإدارية, على الرغم من الأهمية (وإن كانت متوسطة) التي منحها أفراد العينة لتلك الممارسات, إذ تبين أن هناك سيطرة لممارسة الموازنات التخطيطية, وهذا يتفّق بشكل كبير مع الدراسات المتعلقة بالقطاعات الأخرى. أما بالنسبة لممارسات المحاسبة الإدارية غير المستخدمة فإن الدراسة أظهرت أن عدم التبني عائد إلى ضعف المعرفة والخبرة لدى الكادر المحاسبي والإداري, وعدم توفر الدعم المطلوب, على الرغم من وجود المنافسة اللازمة كعامل ضاغط, فضلاً عن عامل كبر حجم هذه المنشآت الذي يشكل حافزاً أساساً لتطبيق هذه الممارسات. The study aimed at exploring the extent of using of management accounting practices in Public Agricultural Firms in Syria, and the importance of this use. In addition, it aimed at knowing which of these practices is the most common and important, and the difficulties of this using. The study was based on a questionnaire, which was distributed on public Agricultural Firms in Syria. There were (42) questionnaires that were distributed on this Society, but (26) questionnaires were completed and retrieved. In spite of the attention paid by the members of the samples to these practices, the results showed great weakness and low level in the application of management accounting practices. As to the management accounting practices which weren’t used, the study showed that the lack of usage is due to the lack of knowledge and experience of the managerial and accounting staff and the absence of the support. This is the case in spite of the presence of competition and the large size of these firms that is a basic factor for the application of these practices.